Pengaruh Penerapan Sistem Informasi Akuntansi, dan Sistem Pengendalian Internal terhadap Kualitas Laporan Keuangan dengan Kompetensi Sumber Daya Manusia sebagai Variabel Moderasi - Aurelia Zarah Kamandita; Suwandi Suwandi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the influence of the application of Accounting Information Systems (AIS), Internal Control Systems (ICS), and Human Resource Competence (HRC) on the quality of financial statements, with HRC as a moderating variable. The research was conducted on financial department employees at Eyelink Group using a quantitative approach and Partial Least Squares (PLS) analysis technique. The findings reveal that AIS and ICS do not have a significant direct impact on the quality of financial statements. However, HRC significantly affects the quality of financial statements. HRC also strengthens the relationship between AIS and the quality of financial statements but does not significantly moderate the relationship between ICS and the quality of financial statements. These findings underscore the importance of competent human resource management to support optimal AIS implementation and improve the quality of financial statements. The study recommends the development of human resource competence through continuous training and education as a strategic measure to enhance financial reporting quality.